2011
DOI: 10.1016/j.lungcan.2011.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Time and dose-related changes in radiological lung density after concurrent chemoradiotherapy for lung cancer

Abstract: Radiation pneumonitis is an important cause of morbidity after concurrent thoracic chemoradiotherapy (CCRT). However, asymptomatic changes in lung density on computed tomography (CT)-scans occur more commonly, and correspond to regions of inflammatory changes. Characterization of dose- and time-related changes in radiological lung density (RLD) may facilitate improved radiation planning, and allow for a more objective measure for assessing damage. We studied changes in RLD following CCRT with cisplatin-etoposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 18 publications
2
20
1
1
Order By: Relevance
“…1c). Since the range of mean density changes measured in the present study was comparable with a study using similar radiotherapy techniques [12], our results suggest that the DS method is more sensitive in detecting radiation damage from CT scans than the Dmean method. DS corresponds better to physician-rated score and symptoms We next investigated whether the DS method corresponds better than the Dmean method to physician-rated pneumonitis.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…1c). Since the range of mean density changes measured in the present study was comparable with a study using similar radiotherapy techniques [12], our results suggest that the DS method is more sensitive in detecting radiation damage from CT scans than the Dmean method. DS corresponds better to physician-rated score and symptoms We next investigated whether the DS method corresponds better than the Dmean method to physician-rated pneumonitis.…”
Section: Resultssupporting
confidence: 85%
“…Besides direct measurements of biological changes, several studies therefore utilized quantitative analysis of CT-scans as a surrogate for histopathological changes after chest radiotherapy [12][13][14]. However to explain a broad range of radiation-induced histopathological changes only (regional) mean density changes of the lung were quantified.…”
Section: S U M M a R Ymentioning
confidence: 99%
“…Phernambucq et al (35) found no relationship between CT scan density changes and increasing dose or RP status, although the authors attributed this result in part to the small sample size (7 patients with RP). To our knowledge, the present study is the first to demonstrate that texture changes following thoracic RT are associated with patient RP status.…”
Section: Discussionmentioning
confidence: 96%
“…The continuous nature of this end-point makes it ideal for radiobiological response modelling. However, the radiological changes may be sub-clinical, and although RP has been shown to correlate with the development of radiologic consolidation on CT [4], a firm association between clinically scored RP and CT density changes has yet to be established for lung cancer patients [5,14]. Low-responsive patients are therefore not necessarily free from symptomatic RP and vice versa.…”
Section: Discussionmentioning
confidence: 99%